ANALISIS KERAWANAN LONGSOR SEBAGAI UPAYA MITIGASI MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI DAERAH LAMPUNG BARAT - Mulyasari, Rahmi; Agustin, Erisa; Yuniza, Nani; Haerudin, Nandi; Riduan, Riduan (Institut Teknologi Sepuluh Nopember, 2024)
The West Lampung area is an area that is prone to landslides, this is due to the high intensity of rainfall and unstable soil structure. In 2022 and 2023, landslide disasters occurred in the West Lampung area which resulted in many losses, so it is necessary to carry out a landslide vulnerability analysis as an anticipatory measure for landslide control measures. By utilizing a geographic information system, geological data, slope, soil type, rainfall and land cover to display areas that are indicated to be prone to landslides. Based on the results of spatial analysis of each landslide-causing parameter, it produces 3 levels of landslide susceptibility classes, namely areas not prone to landslides (95.48 km2), areas prone to landslides (85.85 km2) and areas very prone to landslides (155.43 km2). In areas that are indicated to be vulnerable and very vulnerable, it is necessary to carry out mitigation on sloping areas and land use in these areas.